Efekt nowych funduszy inwestycyjnych (otwartych) akcji w Polsce - Buczek, Sebastian (The new equity mutual funds effect in Poland, 2006)
A discussion on efficient market theory has been alive for the last thirty years. Some market anomalies have been found, however it’s still not clear whether the theory is true or not. I analyzed the investment performance of new Polish equity funds, including new (just set up) funds, in period of 2001-2004. New funds, on average, delivered relatively high returns, far better than WIG index (and “old” funds). Particularly strong performance was delivered by funds managed by fund providers with a long-term track record and managing other large portfolios. The new equity mutual funds effect in Poland can be real because: it’s easier to manage smaller funds than bigger, new funds are charged with lower management fees at the beginning, the managers focus more on new funds to attract interest of potential investors. My study will be continued in the future. The Polish fund market will give an opportunity for such research. In the second half of 2006 and in 2007 new umbrella funds with equity subfunds will be created by many Polish fund providers. Investors who believe in the effect should buy these subfunds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 15-22